372 Single-agent anti-tumor activity in relapsed/refractory solid tumors: interim data from the phase 1 solid tumor trial of AMV564, a novel T-cell engager. (9th November 2020) - Piha-Paul, Sarina; Starodub, Alexander; Karim, Raghad; Shafique, Michael; Suarez, Gabriel Tinoco; Ruegg, Curtis; Smith, Victoria; Chun, Patrick
Abstract : Background: Overcoming the immune-suppressive tumor environment induced by myeloid-derived suppressor cells (MDSC) is a major challenge in immune therapy. AMV564 is a potent conditional agonist that engages T cells to selectively deplete target cells such as MDSC while promoting T cell polarization and activation. Whereas CD33 plays an insignificant role in differentiated myeloid cells, CD33 signaling in immature myeloid cells promotes expansion of MDSC and production of immune-suppressive factors. Preferential binding of AMV564 to areas of high CD33 density enables selective targeting of MDSC. Ex vivo data 1 as well as data from a clinical trial in acute myeloid leukemia (NCT03144245 ) demonstrate the ability of AMV564 to selectively deplete MDSC while sparing monocytes and neutrophils. 2 3 Methods: NCT04128423 is a multi-center Phase 1 study to determine the safety and tolerability, define the maximum-tolerated or pharmacologically active dose, and assess the preliminary efficacy of AMV564. In this 3+3 dose escalation study, patients with advanced solid tumors receive AMV564 once daily via subcutaneous (SC) injection on Days 1–5 and 8–12 of a 21-day cycle. Primary endpoints include incidence, nature and severity of adverse events (AEs). Secondary endpoints include assessment of pharmacokinetics and pharmacodynamics. Results: As of June 30, 2020, 11 patients have been dosed across 3 dose cohorts (15 mcg – 75 mcg). The tumor types enrolled were: colorectal (n=2), GE junction (n=2), pancreatic (n=2), squamous cell carcinoma (n=2), small intestine, ovarian, and endometrial cancer. AMV564 has been well tolerated with no dose-limiting toxicities. The most common treatment-related AEs were fever/pyrexia (Grade 1: n=3; Grade 2: n=8) and injection site reactions (Grade 1: n=1; Grade 2: n=9). Preliminary estimate of median plasma half-life for AMV564 after SC injection was >48 hours, with dose-related increases in peak plasma concentration (Cmax). Tumor responses were evaluable in 9 patients; 1 patient had not reached their first assessment and 1 patient was not efficacy evaluable due to a non-treatment-related AE resulting in study discontinuation. Single-agent activity has been observed including a complete response by RECISTv1.1 criteria in 1 patient with ovarian cancer refractory to all standard therapies and anti-PD-1 therapy, and stable disease in 4 additional patients. Conclusions: AMV564 has been well tolerated across multiple dose levels, with good plasma exposure and evidence of anti-tumor activity when administered subcutaneously. Single-agent anti-tumor activity was observed in an ovarian cancer patient. Acknowledgements: We would like to thank the patients and their families for participating in this clinical trial. Trial Registration: NCT04128423 Ethics Approval: The study was approved by the Institutional Review Board at each center where the study is being conducted. References: Cheng P, Eksioglu E, Chen X, et al. Immunodepletion of MDSC By AMV564, a novel Tetravalent bispecific CD33/CD3 T cell engager restores immune homeostasis in MDS in Vitro . Blood . 2017; 130:51 (abstract). Eckard S, Gehrs L, Smith V, et al. AMV564, a novel bivalent, bispecific T-cell engager, targets myeloid-derived suppressor cells. SITC Annual Meeting; 2019 Nov 6-10. Oral Presentation O71. Westervelt P, Roboz G, Cortes J, et al. Safety and Clinical Activity of AMV564, a CD33/CD3 T-cell Engager, in Patients with Relapsed/Refractory Acute Myeloid Leukemia (AML): Updated Results from the Phase 1 First-in-Human Trial. EHA Annual Congress; 2019 Jun 13-16. Abstract S877.